2007
DOI: 10.1111/j.1365-2133.2007.07961.x
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic potential of human papillomaviruses: a review on the role of host genetics and environmental cofactors

Abstract: Human papillomaviruses (HPVs), with over 100 genotypes, are a very complex group of human pathogenic viruses. In most cases, HPV infection results in benign epithelial proliferations (verrucae). However, oncogenic types of HPV may induce malignant transformation in the presence of cofactors. For example, over 99% of all cervical cancers and a majority of vulval, vaginal, anal and penile cancers are the result of oncogenic HPV types. Such HPV types have been increasingly linked to other epithelial cancers invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 128 publications
(299 reference statements)
1
40
0
1
Order By: Relevance
“…the remaining 5-10% of hpV-infected patients develop long-term infections, and such persistent infections are associated with an increased risk of developing cervical cancer (1). This suggests that, apart from hpV, other factors or co-factors are involved in this process (2). To date, little is known regarding the cellular factors that may facilitate cervical carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the remaining 5-10% of hpV-infected patients develop long-term infections, and such persistent infections are associated with an increased risk of developing cervical cancer (1). This suggests that, apart from hpV, other factors or co-factors are involved in this process (2). To date, little is known regarding the cellular factors that may facilitate cervical carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IGF1 exhibits both endocrine and auto/paracrine activity, respectively. the circulating fraction of iGF1 is transported bound to iGF1 binding proteins (iGF1Bps) types [1][2][3][4][5][6]. the main transporter is IGF1BP3, which modulates the bioactivity of IGF1 by limiting its access to iGF1r (5).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that adverse environmental conditions, such as inappropriate water temperature, may induce immunosuppression in Florida manatees (Halvorsen and Keith, 2008). Immunosuppression, either genetically or environmentally induced, is a well-recognized risk factor for the development of PV-associated diseases (Madkan et al, 2007;Palefsky, 2007). However, seroconversion may occur months after infections, as frequently observed in HPV-infected women (Dillner, 1999;Coursaget, 2003); therefore, we cannot exclude that blood samples from antibody-negative, lesionpositive animals were collected before seroconversion.…”
Section: Discussionmentioning
confidence: 99%
“…The potential oncogenic importance of low-risk types of HPV in the development of laryngeal papillomas is well established, and the predominant types are HPV 6 and 11 Madkan et al, 2007), which are pathogens of laryngeal papillomatosis. According to the clinical characteristics and natural history of disease, four different forms of laryngeal papillomas exist, namely isolated juvenile papillomatosis, juvenile multiple, adult and adult isolated multiple (Madkan et al 2007;Torrente & Ojeda, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%